1993
DOI: 10.1111/j.1365-2044.1993.tb07067.x
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic and hormonal response to cataract surgery

Abstract: SummaryWe studied the metabolic and hormonal responses of 30 elderly patients undergoing routine cataract surgery who were allocated randomly to receive either general anaesthesia, or local anaesthesia by means of either retrobulbar or peribulbar blockade. Both jorms of local anaesthesia successfuIly prevented the increases in circulating cortisol and glucose concentrations seen in those patients who received general anaesthesia, there being no significant diflerences between retrobulbar and peribulbar blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…In contrast, all evaluated parameters except for glucose were reduced markedly during propofol/alfentanil TIVA. These results differ from those reported previously ( 3, 5, 13), where cataract surgery during thiopental/enflurane anesthesia was associated with substantial adrenergic activation. Although the number of studied patients was small and included only ASA physical status 1 and 2 patients, it is apparent that local anesthesia produces the best adrenergic and hemodynamic stability during cataract surgery.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, all evaluated parameters except for glucose were reduced markedly during propofol/alfentanil TIVA. These results differ from those reported previously ( 3, 5, 13), where cataract surgery during thiopental/enflurane anesthesia was associated with substantial adrenergic activation. Although the number of studied patients was small and included only ASA physical status 1 and 2 patients, it is apparent that local anesthesia produces the best adrenergic and hemodynamic stability during cataract surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors concluded that “local anesthesia prevented the increase in plasma norepinephrine, epinephrine, and glucose concentrations found in those patients who received general anesthesia” ( 5). In a further study the same group compared two methods of local anesthesia: retrobulbar and peribulbar blockade ( 3). There were no significant changes in blood glucose, serum cortisol, or blood lactate concentration with either technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Some of its merits include ease of administration, preservation of consciousness, good postoperative analgesia, reduced stress response, early mobilization, and discharge of patients as well as minimal respiratory and cardiovascular systems complications. 2 3 4 5 Regional anesthesia has been popularized in ophthalmic surgery because of its high success rate and a wide margin of safety. 4 It ensures quicker patient recovery thereby enabling day-surgery cases and reduction in cost of surgery.…”
Section: Introductionmentioning
confidence: 99%